STRATEGIC MANAGEMENT OF HIGHER EDUCATION BASED ON LOCAL MALAY WISDOM (Case Study of STAI TEBINGTINGGI DELI) - M. Alang Khairun Nizar (RADJA PUBLIKA, 2025)
Research based on Most of the people of Tebing Tinggi no longer remember the history and values ​​of the culture. ThereforeSTAI Tebingtinggi Deli, which is a college under the auspices of the Ministry of Religion which has been operating since 1999, is located in Tebingtinggi City.STAI Tebing Tinggi As a college that focuses on Islamic studies, STAI Tebing Tinggi Deli plays a role in maintaining and preservingculture by making local wisdom the main vision and mission in the master plan for developing higher education.This research aims DiscloseFormula, implementation and evaluation of Higher Education Strategy based on Malay local wisdom at STAI Tebingtinggi Deli. In order to obtain a complete, in-depth and comprehensive understanding of the focus of this research, the researcher uses a phenomenological paradigm with a qualitative approach and case study type. Data were collected with a natural setting as a direct data source. This research is expected to reveal phenomena and symptoms in depth, find out comprehensively and completely and describe Higher Education Strategy Management Based on Malay local wisdom at STAI Tebingtinggi Deli. The results of the study show that the Curriculum Formulation of STAI Tebingtinggi Deli in realizing the achievement of knowledge, insight and personality according to Malay local wisdom produces a course on the History of Malay and Islamic civilization. Therefore, all study programs at STAI Tebingtinggi Deli (PAI, BKPI, MBS, PIAUD and KPI) require all students to take 2 credits of lectures in semester 2. In addition, to support higher education institutions based on Malay local wisdom, STAI Tebingtinggi Deli has established cooperation with the sultanate or Malay traditional leaders in the city of Tebing Tinggi and its surroundings.